GAMBARAN PENGETAHUAN MASYARAKAT DESA WIAU LAPI TENTANG STOMATITIS AFTOSA REKUREN - Wololy, Jefrianto; Kepel, Billy J.; Mintjelungan, Christy N. (UNIVERSITAS SAM RATULANGI, 2013)
Abstract: Recurrent aphthous stomatitis (RAS), commonly known among Indonesian people as